Development of Large-Horned Cattle Breeding in the Republic of Karakalpakstan and its Territorial Characteristics - Turdimambetov I.R.; Joldasov A.S. (Genius Journals, 2023)
The dynamics of cattle breeding in the Republic of Karakalpakstan and issues of its territorial organization are studied in this article
Keywords: Livestock; large-horned cattle; land fund; pasture fund